Age-dependent dendrobine biosynthesis in Dendrobium nobile: insights into endophytic fungal interactions - Zhao, Yongxia; Ji, Xiaolong; Liu, Xiaoqi; Qin, Lin; Tan, Daopeng; Wu, Di; Bai, Chaojun; Yang, Jiyong; Xie, Jian; He, Yuqi (Frontiers in Microbiology, 2023)
Dendrobium nobile (D.nobile), a valued Chinese herb known for its diverse pharmacological effects, owes much of its potency to the bioactive compound dendrobine. However, dendrobine content varies significantly with plant age, and the mechanisms governing this variation remain unclear. This study delves into the potential role of endophytic fungi in shaping host-microbe interactions and influencing plant metabolism. Through a comprehensive analysis of endophytic fungal communities and host gene expression in D. nobile stems of varying ages, we aim to identify associations between specific fungal taxa and host genes. Using RNA-seq, we examined the transcriptomes of 1-year-old, 2-year-old, and 3-year-old D. nobile samples, revealing 192 differentially expressed host genes. These genes exhibited a gradual decrease in expression levels as the plants aged, mirroring dendrobine content changes. They were enriched in 32 biological pathways, including phagosome, fatty acid degradation, alpha-linolenic acid metabolism, and plant hormone signal transduction. Furthermore, a significant shift in the composition of the fungal community within D. nobile stems was observed along the age gradient. Olipidium, Hannaella, and Plectospherella dominated in 1year-old plants, while Strelitziana and Trichomerium prevailed in 2-year-old plants. Conversely, 3year-old plants exhibited additional enrichment of endophytic fungi, including the genus Rhizopus. Two gene expression modules (mediumpurple 3 and darkorange) correlated significantly with dominant endophytic fungi abundance and dendrobine accumulation. Key genes involved in dendrobine synthesis were found associated with plant hormone synthesis. This study suggests that the interplay between different endophytic fungi and the hormone signaling system in D. nobile likely regulates dendrobine biosynthesis, with specific endophytes potentially triggering hormone signaling cascades that ultimately influence dendrobine synthesis.